2003
DOI: 10.1051/0004-6361:20030248
|View full text |Cite
|
Sign up to set email alerts
|

Long term disc variability in the Be staroAndromedae

Abstract: Abstract. We present 18 years of high resolution and S/N Hα spectroscopy of the Be shell star o And, obtained between 1985And, obtained between -2002. Spectra taken during late 1985 show a pure photospheric profile, with disc re-formation commencing in 1986; a process that is found to occur over long timescales (∼10 3 days). Analysis of the evolution of the properties of the Hα shell profile suggest that the disc kinematics are dominated by rotational motion. It has been shown that disc loss in o And occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 26 publications
7
37
0
3
Order By: Relevance
“…However, as first noted by Struve (1931) rapid (critical) stellar rotation seems to play the key role. Studies on disk formation around the most rapidly rotating stars known, i.e., the classical Be stars, revealed that their disks are most probably driven by viscosity (see, e.g., Porter 1999;Okazaki 2001;Jones et al 2008), resulting in quasi-Keplerian rotating disks with a slow (few km s −1 ) equatorial outflow component, in agreement with observations (Clark et al 2003). The star S 65 also seems to be rotating (close to) critical.…”
Section: Possible Disk Formation Mechanismsupporting
confidence: 79%
“…However, as first noted by Struve (1931) rapid (critical) stellar rotation seems to play the key role. Studies on disk formation around the most rapidly rotating stars known, i.e., the classical Be stars, revealed that their disks are most probably driven by viscosity (see, e.g., Porter 1999;Okazaki 2001;Jones et al 2008), resulting in quasi-Keplerian rotating disks with a slow (few km s −1 ) equatorial outflow component, in agreement with observations (Clark et al 2003). The star S 65 also seems to be rotating (close to) critical.…”
Section: Possible Disk Formation Mechanismsupporting
confidence: 79%
“…The B6e star o And has also experienced shell and diskloss episodes, as discussed in (Clark et al 2003). Their Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Arguably the most dramatic type of variability observed is the aperiodic "Be to normal B to Be" transition whereby classical Be stars dissipate (i.e., lose) their disks, and will often begin to regenerate a new disk after a period of relative quiescence (see, e.g., Underhill & Doazan 1982 and references therein). While several individual stars have been observed to experience this transition one or more times (Underhill & Doazan 1982;Doazan et al 1983;Clark et al 2003;Vinicius et al 2006), it is not known whether there is a characteristic timescale for disk loss and regeneration that would suggest a singular disk formation mechanism or whether each event is unique. Although their sample size is small, recent monitoring of eight open clusters by McSwain et al (2009) has revealed a surprising 12 new transient Be stars out of a sample of 296 stars monitored, suggesting that disk-loss/renewal episodes may be a prevalent phenomenon.…”
Section: Introductionmentioning
confidence: 99%